2003
DOI: 10.1007/s00264-003-0457-6
|View full text |Cite
|
Sign up to set email alerts
|

Implant-related complications in the treatment of unstable intertrochanteric fractures: meta-analysis of dynamic screw-plate versus dynamic screw-intramedullary nail devices

Abstract: The choice between dynamic screw-intramedullary nail (DSIN) devices and dynamic screw-plate (DSP) devices for the fixation of unstable trochanteric fractures remains controversial. This study presents a meta-analysis of fixation failures in unstable trochanteric femoral fractures using DSP devices or DSIN devices. Two independent assessors selected randomised controlled trials using a range of electronic databases, as well as reference lists of selected articles. A study quality checklist was used. The occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
54
0
3

Year Published

2004
2004
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(58 citation statements)
references
References 22 publications
1
54
0
3
Order By: Relevance
“…So the choice of the implant is particularly critical in unstable fractures. This is reflected in the clinical situation where the failure rate in unstable fractures is significantly increased compared to stable fractures [1,21,29]. Although these complications in unstable fractures are largely related to the local mechanical situation at the fracture site, no standardized biomechanical model exists to study the mechanical characteristics of hip fracture osteosynthesis [12].…”
Section: Introductionmentioning
confidence: 99%
“…So the choice of the implant is particularly critical in unstable fractures. This is reflected in the clinical situation where the failure rate in unstable fractures is significantly increased compared to stable fractures [1,21,29]. Although these complications in unstable fractures are largely related to the local mechanical situation at the fracture site, no standardized biomechanical model exists to study the mechanical characteristics of hip fracture osteosynthesis [12].…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis of 17 randomized studies comparing dynamic screw IM nailing devices (DSIN) and dynamic screw-plate devices for unstable intertrochanteric fractures found no significant difference in the occurrence of screw cut-out among the different devices. 5 The authors concluded that significant controversy remains as DSIN devices seem to reduce cutout in studies on unstable fractures while the opposite is true for studies combining stable and unstable fractures. No clear clinical advantage was identified in either device.…”
mentioning
confidence: 99%
“…1 The cutout rate for intramedullary (IM) nails has been reported to be as high as 8.3%. 1,5 Screw cut-out or migration can occur in either an axial or cephalad direction or a combination of both. Axial migration is also referred to as ''axial penetration'' or ''axial impaction.''…”
mentioning
confidence: 99%
“…Potential disadvantages are related to greater risk of jamming of the sliding mechanism and stress risers at the site of the tip of the nail and distal locking bolts. It has been suggested, without supporting clinical data, that the IMNs are superior for unstable trochanteric fractures, reverse oblique fractures and sub-trochanteric fractures [2,3]. Controversy, therefore, continues regarding the optimum choice of implant for these unstable fractures [14].…”
Section: Introductionmentioning
confidence: 99%